PERAN DAN TANGGUNG JAWAB NOTARIS ATAS PEMBUATAN PERJANJIAN NOMINEE SEBAGAI UPAYA PENYELUNDUPAN HUKUM YANG DILAKUKAN PENGHADAP - Aurelia Libertina Nadeak; Jelly Nasseri; Mulyadi Mulyadi; Mulyadi (Journal of Innovation Research and Knowledge, 2026)
Notaries are authorized to make authentic deeds with the obligation to guarantee legal certainty. However, the practice of making nominee agreements is often misused as a form of legal smuggling, especially regarding restrictions on foreign ownership. This raises issues regarding the responsibility of notaries which are generally only based on the formal truth of the parties' statements. This study highlights the authority, responsibility, and supervision of notaries in relation to nominee agreement deeds. The formulation of the research problem is, what is the role of Notaries in the making of nominee agreements that are suspected of being a legal smuggling attempt and what is the legal responsibility of Notaries for nominee agreements that are suspected of being a legal smuggling attempt. The legal theories applied as analytical tools are the responsibility theory of Hans Kelsen and the agreement theory of R. Subekti. The method used in this research is a normative juridical research type, namely library legal research by using secondary data. The writing approaches used are the statutory approach, conceptual approach, analytical approach, and case approach. The legal material collection technique is carried out by identifying and inventorying positive legal regulations, book literature, journals, and other legal material sources. For legal material analysis techniques, grammatical interpretation, systematic interpretation, and legal construction methods are used. Nominee agreements granting access to land ownership to foreign nationals violate Articles 21 and 26 of the Basic Agrarian Law. According to Hans Kelsen, this violation automatically gives rise to legal liability for notaries, regardless of the parties' intentions. From Subekti's perspective, nominee agreements are invalid because they violate the law and therefore do not create a binding contract. Therefore, notaries remain liable for the deeds they create, whether civil, administrative, or criminal.